The Application of International Laws in Bangladesh: A Critical Evaluation - Mazharul Islam; Mohammed Tahmidul Islam; Md. Tuhin Mia; Md. Zahidul Islam (Universitas Negeri Semarang, 2022)
This article discusses the incorporation and implementation of international laws, specifically international treaties and agreements into the domestic legal system of Bangladesh. The position of international laws in the legal system of Bangladesh and their authority to interpret and challenge domestic laws has been focused upon. To that effect, the constitutional provisions dealing with international law along with various authoritative court decisions have been analyzed. Additionally, status and implementation of customary international laws in Bangladesh have also been absorbed. How the norms of customary international laws are being incorporated and implemented have been discussed in detail. The analytical methods of research have been carried in the piece highlighting judicial decisions and international instruments. This article is based on secondary materials with the key sources including textbooks, reports, journal articles, conference papers, daily newspapers and online documents. The study has also relied on international instruments, domestic laws and decided cases of Apex Court of Bangladesh. The findings show that as a democratic country Bangladesh needs to incorporate for the sake of its own people the provisions of international treaties into domestic laws. This is a gradual but perilous process which would take more than political goodwill to materialize. As a young nation, it still has a long way to go to level its regulations up-to the international standards. The positive indication is that the supreme courts of Bangladesh are increasingly realizing and interpreting international instruments through their decisions pressurizing the government to make positive changes in the legislations.